A new species of Mastostethus (Coleoptera: Chrysomeloidea: Megalopodidae) from Chiapas, Mexico - Rodríguez-Mirón, Geovanni M. (Zootaxa, 2019)
Mastostethus mulier sp. nov., from Chiapas, Mexico is described and illustrated.